2013
DOI: 10.1371/journal.pone.0060986
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cyclic Nucleotide-Dependent Actin Cytoskeletal Dynamics: [Ca2+]i and Force Suppression in Forskolin-Pretreated Porcine Coronary Arteries

Abstract: Initiation of force generation during vascular smooth muscle contraction involves a rise in intracellular calcium ([Ca2+]i) and phosphorylation of myosin light chains (MLC). However, reversal of these two processes alone does not account for the force inhibition that occurs during relaxation or inhibition of contraction, implicating that other mechanisms, such as actin cytoskeletal rearrangement, play a role in the suppression of force. In this study, we hypothesize that forskolin-induced force suppression is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 57 publications
(84 reference statements)
1
24
0
Order By: Relevance
“…Of note, of 6 studies focusing especially on VSM, 5 reported increased cofilin phosphorylation in response to contractile stimulation. 39,[44][45][46][47] If one can conclude that vasodilation should lead to opposite changes, the majority of these studies are consistent with cofilin dephosphorylation being a relevant factor in controlling cytoskeletal changes, which ultimately lead to vasodilation. However, one vascular study also reported decreased phosphorylation with contraction.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Of note, of 6 studies focusing especially on VSM, 5 reported increased cofilin phosphorylation in response to contractile stimulation. 39,[44][45][46][47] If one can conclude that vasodilation should lead to opposite changes, the majority of these studies are consistent with cofilin dephosphorylation being a relevant factor in controlling cytoskeletal changes, which ultimately lead to vasodilation. However, one vascular study also reported decreased phosphorylation with contraction.…”
Section: Discussionmentioning
confidence: 61%
“…39,[44][45][46][47] By contrast, in airway smooth muscle ADF (actin depolymerizing factor)/cofilin dephosphorylation was reported to occur during constriction, that is, a condition that goes along with actin polymerization. 48 We cannot explain the conflicting results at present, but differences between VSM and other tissues or the mode of preactivation of the muscle may play a role here.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations by our laboratory demonstrated that P20 peptide caused relaxation of vascular smooth muscle by inducing actin depolymerization (24,30,33), and we hypothesized that P20 peptide would also cause actin depolymerization in ASM. Therefore, we measured the actin concentration in intact PASM tissue, as PASM samples have less heterogeneity compared with HASM samples.…”
Section: P20 Peptide Treatment Decreases F-actin Levels In Intact Asmmentioning
confidence: 91%
“…Phosphorylation of HSP20 in response to bronchodilators was examined by isoelectric focusing, which separates the phospho and nonphospho forms of HSP20, and phospho-HSP20 level was measured by Western blotting, as described previously (30).…”
Section: Hsp20 Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation